RANK Ligand Helps Immunity to Leishmania major by Skewing M2-Like Into M1 Macrophages - Rigoni, Thaís S.; Vellozo, Natália S.; Cabral-Piccin, Mariela; Fabiano-Coelho, Laryssa; Lopes, Ulisses G.; Filardy, Alessandra A.; DosReis, George A.; Lopes, Marcela F. (Frontiers in Immunology, 2020)
Macrophages host Leishmania major infection, which causes cutaneous Leishmaniasis in humans. In the murine model, resistance to infection depends on the host immunity mediated by CD4 T-cell cytokines and macrophages. In association to other stimuli, the Th1 cytokine IFN-γ induces NO-mediated microbial killing by M1/classically-activated macrophages. By contrast, the Th2 cytokine IL-4 promotes M2/alternatively activated macrophages, which express arginase-1 and shelter infection. Other cytokines, such as RANKL, might also participate in the crosstalk between T cells and macrophages to restrict parasite infection. RANKL and its receptor RANK are known to play an essential role in bone remodeling, by inducing osteoclatogenesis. It has also been shown that RANKL stimulates antigen-presenting cells, such as DCs and macrophages, to enhance T cell responses. Here we investigated how RANKL directly modulates the effector macrophage phenotypes and immunity to L. major parasites. We found that inflammatory peritoneal macrophages from B6 mice express RANK and M2 features, such as CD301 (MGL) and CD206 (mannose receptor). Nonetheless, treatment with RANKL or IFN-γ induced macrophage differentiation into more mature F40/80hi macrophages able to produce IL-12 and TNF-α. In parallel, macrophages treated with RANKL, IFN-γ, or RANKL along with IFN-γ progressively downregulated the expression of the M2 hallmarks MGL, arginase-1, and CCL17. Moreover, a synergism between IFN-γ and RANKL enhanced inducible NO synthase (iNOS) expression and NO production by macrophages. These results are consistent with the idea that RANKL helps IFN-γ to induce a M2-like to M1 phenotype shift. Accordingly, concomitant treatment with RANKL and IFN-γ promoted macrophage-mediated immunity to L. major, by inducing NO and ROS-dependent parasite killing. Furthermore, by cooperating with IFN-γ, endogenous RANKL engages CD4 T-cell help towards L. major-infected macrophages to upregulate M1 and Th1 cytokine responses. Therefore, RANKL, in combination with IFN-γ, is a potential local therapeutic tool to improve immune responses in Leishmaniasis, by skewing M2-like into effector M1 macrophages.